Ion and Neutron Beams Discover New Facts from History. (2nd October 2017) - Macková, Anna; Kučera, Jan; Kameník, Jan; Havránek, Vladimír; Kranda, Karel
Abstract : Nuclear physics applications in medicine and energy are well known and widely reported. For example, the recent report "Nuclear Physics for Medicine, " published by the European Science Foundation[1] or "Energy for the Future: The Nuclear Option, " written by scientists at the European Physical Society (EPS)[2] can be mentioned. Less well known are the many important nuclear and related techniques to study objects of cultural heritage. There has been enormous progress in this field in recent years and our current contribution provides some snippets of the comprehensive topical paper "Nuclear Physics for Cultural Heritage" published by the EPS recently[3], which aims for a popular and accessible account showing the broad nuclear physics applications in cultural heritage investigation and preservation. Nuclear Physics contributes to archaeometry mainly by non-invasive investigation of cultural heritage objects with ion and neutron beams.